Rotavirus disease (gastroenteritis) in children with diarrhea (0-5 years): Determined prevalence in selected hospitals of Sokoto City, Nigeria - Salisu Garba; Malami Dikko; Barga Isiyaka Bala; Zayyanu Malami; Yusuf Sarkingobir; Sabiu Muhammad (Journal of Community Service in Science and Engineering (JoCSE), 2023)
Rotavirus is the most common cause of severe diarrhea among children under five years of age worldwide. This study was conducted to detect the prevalence of Rotaviruses in children attending selected hospitals in Sokoto State. Three hundred fifty stool samples were collected from diarrheic children under five years of age. Samples were analyzed for Group A rotavirus antigens using the CUSABIO Human Rotavirus (RV Ag) ELISA kit. Rotaviruses were detected in stool samples of 53/350 children, given a 15.1% prevalence, with the infection occurring throughout the study period. The percentage of Rotavirus infections was 52.8% and 47.2 % among males and females, respectively. The Rotavirus cases were significantly higher in children below two years of age 32/53 (60.4%) than children between 2-5 years of age 21/53 (39.6%). The result further showed that 35/53(66.1%) of the positive cases exhibited three major symptoms of the disease, while 13/53 (24.5%) exhibited diarrhea with either fever or vomiting, while 9.4%(5/53) showed only diarrhea. Vaccination and other related interventions, including routine diagnosis, should be provided to safeguard public health against the Rotavirus. Rotavirus adalah penyebab paling umum diare parah pada anak di bawah lima tahun di seluruh dunia. Penelitian ini dilakukan untuk mendeteksi prevalensi Rotavirus pada anak-anak yang dirawat di rumah sakit tertentu di Negara Bagian Sokoto. Tiga ratus lima puluh sampel tinja dikumpulkan dari anak-anak di bawah usia lima tahun yang menderita diare. Sampel dianalisis untuk antigen rotavirus Grup A menggunakan kit ELISA CUSABIO Human Rotavirus (RV Ag). Rotavirus terdeteksi pada sampel tinja 53/350 anak, dengan prevalensi 15,1%, dengan infeksi terjadi sepanjang masa penelitian. Persentase infeksi Rotavirus masing-masing adalah 52,8% dan 47,2% pada laki-laki dan perempuan. Kasus Rotavirus secara signifikan lebih tinggi pada anak-anak di bawah usia dua tahun 32/53 (60,4%) dibandingkan anak-anak antara usia 2-5 tahun 21/53 (39,6%). Hasilnya lebih lanjut menunjukkan bahwa 35/53 (66,1%) dari kasus positif menunjukkan tiga gejala utama penyakit, sementara 13/53 (24,5%) menunjukkan diare disertai demam atau muntah, sedangkan 9,4% (5/53) hanya menunjukkan gejala penyakit yang sama. diare. Vaksinasi dan intervensi terkait lainnya, termasuk diagnosis rutin, harus diberikan untuk menjaga kesehatan masyarakat terhadap Rotavirus.